The Meaning of Success Among Single Career Women Aged 30–40: an Indonesian Indigenous Psychology Perspective - Indira Mustika Tandiono; Puput Mariyati (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2026)
Indonesia is witnessing a growing number of single, career-oriented women aged 30–40, particularly in urban areas. They continue to face social pressure rooted in collectivistic and patriarchal values equating women's success with marriage and motherhood. This study aims to explore how single career women construct and interpret the meaning of success from an indigenous Indonesian psychology perspective. A qualitative approach using Interpretative Phenomenological Analysis (IPA) was employed with three purposively selected participants representing variation in ethnicity, religion, and career field. Data was gathered through in-depth interviews and daily reflective diaries. Findings reveal that the meaning of success shifted from a material and achievement-oriented definition toward a process-based orientation centered on small, daily, gratitude-laden experiences, inner peace, and consistency in upholding spiritual values rooted in local wisdom and religiosity. These findings affirm the relevance of an indigenous psychology approach in understanding success as inseparable from religiosity, family values, social relations, and local cultural wisdom, contributing to culturally sensitive psychological practice and challenging the stigma attached to unmarried career women in Indonesia.